Fatty acids produced by the gut microbiota dampen host inflammatory responses by modulating intestinal SUMOylation - Chaima Ezzine; Léa Loison; Nadine Montbrion; Christine Bôle-Feysot; Pierre Déchelotte; Moïse Coëffier; David Ribet (Gut Microbes)
The gut microbiota produces a wide variety of metabolites, which interact with intestinal cells and contribute to host physiology. The effect of gut commensal bacteria on host protein SUMOylation, an essential ubiquitin-like modification involved in various intestinal functions, remains, however, unknown. Here, we show that short chain fatty acids (SCFAs) and branched chain fatty acids (BCFAs) produced by the gut microbiota increase protein SUMOylation in intestinal cells in a pH-dependent manner. We demonstrate that these metabolites inactivate intestinal deSUMOylases and promote the hyperSUMOylation of nuclear matrix-associated proteins. We further show that BCFAs inhibit the NF-κB pathway, decrease pro-inflammatory cytokine expression, and promote intestinal epithelial integrity. Together, our results reveal that fatty acids produced by gut commensal bacteria regulate intestinal physiology by modulating SUMOylation and illustrate a new mechanism of dampening of host inflammatory responses triggered by the gut microbiota.